Active acoustic leak detection in a pressurized PVC pipe. Issue 4 (20th April 2020) - Kafle, Marshal Deep; Narasimhan, Sriram
ABSTRACT: Water distribution systems are critical infrastructure elements conveying water through thousands of kilometers of pipes. Pipes – one of the most critical elements in such systems – are subjected to various structural and environmental degradation mechanisms, eventually leading to leaks and breaks. Much of the literature on leak detection has focused on passive methods; recording and analyzing acoustic signatures produced by leak(s) from passive piezo acoustic or pressure devices. In this paper, an active method is proposed where an acoustic source is used to excite a pressurized PVC pipe and the measured reflected and transmitted energy using hydrophone receivers is used to determine the presence of a leak. Experimental tests employing continuous sine and white noise excitation and the underpinning theory which supports experimental observations are presented. Experimental results show that this method can detect leaks robustly and has significant potential for use in pressurized water distribution systems.